Flame retardants, dioxins, and furans in air and on firefighters' protective ensembles during controlled residential firefighting. (July 2020) - Fent, Kenneth W.; LaGuardia, Mark; Luellen, Drew; McCormick, Seth; Mayer, Alexander; Chen, I-Chen; Kerber, Steve; Smith, Denise; Horn, Gavin P.
Highlights: Several flame retardants, dioxins, and furans were measured in air during controlled residential fires. Some of these compounds were detected in air during overhaul, supporting the use of respiratory protection. Firefighters' turnout gear, including gloves, became contaminated with many of these compounds. Routine gross on-scene decontamination of turnout gear appeared to reduce many of these compounds. Abstract: Introduction: Structure fires that involve modern furnishings may emit brominated flame retardants (BFRs) and organophosphate flame retardants (OPFRs), as well as brominated and chlorinated dioxins and furans, into the environment. Objectives: The goal of this study was to quantify the airborne and personal protective equipment (PPE) contamination levels of these compounds during controlled residential fires in the U.S., and to evaluate gross-decontamination measures. Methods: Bulk-sampling was done to confirm the presence of flame retardants (FRs) in the furnishings used in 12 controlled residential structure fires. Area air samples were collected during the fires and PPE wipe samples were collected from the firefighters' turnout jackets and gloves after firefighting. For each fire, half of the jackets were decontaminated and the other half were not. Results: Of the BFRs and OPFRs measured in air during the fire period, decabromodiphenyl ether (BDE-209) and triphenyl phosphate (TPP) were the most abundant, with medians of 15.6 and 408 µg/m 3, respectively, and were also detected during overhaul. These and several other BFRs and OPFRs were measured on PPE. Some gloves had contaminant levels exceeding 100 ng/cm 2 and were generally more contaminated than jackets. Air and surface levels of the brominated furans appeared to be higher than the chlorinated dioxins and furans. Routine gross decontamination appeared to reduce many of the BFR contaminants, but results for the OPFRs were mixed. Conclusions: Structure fires are likely to result in a variety of FRs, dioxins, and furans into the environment, leading to PPE contamination for those working on the fireground. Firefighters should wear self-contained breathing apparatus during all phases of the response and launder or decontaminate their PPE (including gloves) after fire events.